1961
DOI: 10.1037/h0045416
|View full text |Cite
|
Sign up to set email alerts
|

A factor analysis of the California Psychological Inventory.

Abstract: CM CO CO NO CM 00 LO co ON TH NO TH CM TjH 00 "* NO iH CM* CM* «-i © © *H r-H* d d CM *H TH ^H* ,-J d T^ CM* d O 00 ON ^H O ON' CM* d d O >o NO NO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1967
1967
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 5 publications
(1 reference statement)
1
18
0
Order By: Relevance
“…Since the 18 scales of the CPI tend to show appreciable intercorrelation it was necessary to determine the independent dimensions represented. Although Gough has grouped these scales into four classes: (1) Poise, Ascendancy, and Self-assurance; (2) Socialization, Maturity, and Responsibility; (3) Achievement Potential and Intellectual Efficiency; and (4) Intellectual and Interest Modes, his groupings are not readily replicated ( Crites, Bechtoldt, Goodstein, & Heilbrun, 1961;Leton & Walter, 1961;Mitchell & Pierce-Jones, 1960;Shure & Rogers, 1963). We therefore performed separate factor analyses for each of the present samples.…”
Section: Procedures and Designmentioning
confidence: 84%
“…Since the 18 scales of the CPI tend to show appreciable intercorrelation it was necessary to determine the independent dimensions represented. Although Gough has grouped these scales into four classes: (1) Poise, Ascendancy, and Self-assurance; (2) Socialization, Maturity, and Responsibility; (3) Achievement Potential and Intellectual Efficiency; and (4) Intellectual and Interest Modes, his groupings are not readily replicated ( Crites, Bechtoldt, Goodstein, & Heilbrun, 1961;Leton & Walter, 1961;Mitchell & Pierce-Jones, 1960;Shure & Rogers, 1963). We therefore performed separate factor analyses for each of the present samples.…”
Section: Procedures and Designmentioning
confidence: 84%
“…These data were obtained from University records. Because the Dominance, Sociability, Self-acceptance and Intellectual Efficiency scales were found to comprise a factor measuring poise, ascendance and self-assurance (Crites, 1961;1964), a multiple correlation was computed between these four scales and the measure of unwarranted confidence.…”
Section: Methodsmentioning
confidence: 99%
“…A factor analysis of the CPI responses of school administrators by Pierce -Jones, et al, ( 1962) suggested that Factor I11 might appropriately be called Rigid Conformity to Convention. Studies by Crites, et al, (1961) and Springob and Struening (1964) indicated that the terms Inflexibility or Rigidity best described composite scale loadings for this factor.…”
Section: Rigidity Us a Predictormentioning
confidence: 97%
“…Springob and Struening suggest that Factor I, which includes high loadings of CPI scales purporting to measure such traits as self-control (Sc) , desire to create a good impression (Gi), sense of well-being (Wb), taler,ance (To), achievement-via-conformity ( Ac) , psychological-mindedness (Py), and socialization (So), was measuring a concern with the presentation of self. Crites, Bechtoldt, Goodstein, and Heilbrun ( 1961) labeled a factor with comparable scale loadings the "good impression" factor, a name which has similar implications.…”
Section: Social Desirability As a Predictormentioning
confidence: 99%
See 1 more Smart Citation